Kajian Normatif Penanganan Pengungsi Dan Pencari Suaka berdasarkan Peraturan Presiden No. 125 Tahun 2016 dan Konvensi 1951 tentang Status Pengungsi - Muh Fanny Chamdani; Himuyatul Hasanah (FAIRNESS AND JUSTICE, 2020)
This study aims to obtain a description of Refugee Handling from Abroad in accordance with Presidential Regulation No. 125 of 2016 concerning Handling of Refugees from Abroad. As a country that recognizes, respects and upholds human rights, Indonesia therefore recognizes and respects the right to security from refugees and asylum seekers. Therefore the government of the Republic of Indonesia made regulations regarding the legal protection of refugees and asylum seekers.